Optical Properties of Cellulose Esters and Applications to Optical Functional Films - Abd Manaf, Mohd Edeerozey (Smithers Rapra Technology Ltd, 2013)
Cellulose esters are also employed for optical displays such as a liquid crystal display. In this application, various types of polymer films are required to construct a display, such as antiglare film, retardation film, protective film, brightness enhancement film and diffusion film. In particular, polarisation is an extremely important property for retardation and protective films. This property is expressed by birefringence Δn. In the case of oriented polymer films, the birefringence can be controlled by varying the stretching ratio. Consequently, it is always used for a retardation film that gives a specific retardation (Γ = d Δn; d is the film thickness). Another important optical film used in displays is the protective film, which is used to protect a polariser from moisture. Therefore, it has to be free from birefringence so that the polarised light will not be disturbed.